KAJIAN GENDER DALAM CERPEN KUKILA KUMPULAN CERPEN KARYA A. AAN MANSYUR - Iswan Afandi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The purpose of this study is to analyze and describe the phenomenon of gender in short stories with a feminist approach. This study used a descriptive qualitative method with content analysis techniques. Data collection was carried out by a descriptive survey through relevant research article data sources, library data sources, printed books containing a collection of Aan Mansyur's short stories published by PT Gramedia Pustaka Utama in 2012. The analysis focused on the Mansyur author's thinking, social issues, traditional culture, and modern culture regarding women. The results of the study, namely the type of feminist used by the author Mansyur is existential feminism. In this case, the mother character in the short story in the Coconut Gardens in my Head shows its existence as a human being who can compete in the public sphere. Auntie Mare can pay for her children's education by working. In terms of culture, there has been a change from traditional to modern culture. Aunt Mare's character is no longer employed as ata or slave in the Bone tradition but is given a job as a gardener and barber. Generally, this work is carried out by men but through the author Mansyur, the job is taken over by women. Mansyur's short story found the phenomenon of gender injustice including marginalization, subordination, stereotyping, physical violence, and workload problems